Performance bonuses and effort: Evidence from fight night awards in mixed martial arts - Paul Gift (International Journal of Financial Studies, 2019)
This paper investigates the role of fight night bonus awards on fighter behavior in the Ultimate Fighting Championship (UFC) and World Extreme Cage (WEC) fighting mixed martial arts (MMA) promotions. Behavior is analyzed using detailed fighter performance statistics, exploiting variation in bonus size across events and over time. Findings suggest that fighters are not meaningfully influenced by bonus levels within the range observed in the sample period and possible explanations are discussed. Fight night bonuses appear to serve as a lottery compensation mechanism to ex post reward performances consistent with an MMA promotion's desires rather than ex ante incentivize such performances. Findings have implications for strategic MMA promoter decisions and contribute more broadly to the personnel economics literature on incentives and compensation.
Keywords: J33; M52; Z22; 330; bonuses; effort; fighter performance; mixed martial arts (MMA); Ultimate Fighting Championship (UFC); World Extreme Cagefighting (WEC); Zuffa LLC